Women in IT : Inspiring the next generation. - IT, BCS The Chartered Institute for (BCS Learning & Development Limited, 2014)
Foreword Preface 1. Some background 2. IT professionals 2.1 Entrepreneurs 3. Academics 4. An interview with Karen Spaerck-Jones 5. Useful links.